Pharmacological and other treatment modalities for esophageal pain. Issue 1 (21st July 2016) - Hoff, Dag Arne Lihaug; Brock, Christina; Farmer, Adam D.; Dickman, Ram; Ruffle, James K.; Shaker, Anisa; Drewes, Asbjørn M.
Abstract : Treatment of esophageal pain remains a major challenge for the clinician. Although many patients have heartburn and may respond to proton pump inhibitors, there in an unmet need for other treatment modalities in patients where there are no obvious pathological findings. Although analgesics are the mainstay in esophageal pain treatment, many patients are nonresponders to these drugs. The current concise review focuses on other systems affecting pain processing, where better understanding may serve as a framework for therapy. These are the parasympathetic nervous system, exercise, and personality profiles. Finally, treatment with analgesics for functional chest pain remains a challenge, and an overview of treatment with antidepressive drugs is provided.